О развитии исследований трансформаций лесного комплекса - Anuchin A. S. (Образовательная среда сегодня: стратегии развития, 2016)
It shows that in recent years published a series of papers that will be useful for further study of the transformations of the domestic timber industry.
Keywords: лесной комплекс; направления исследований; трансформации; forest complex; transformation; areas of research